A CORE AND VALENCE LEVEL PHOTOEMISSION-STUDY OF Y1-XPRXBA2CU3O7 - Cohen, O; Potter, F; Rastomjee, C; Egdell, R (1992)
Core and valence level photoemission spectra of the 123 oxides Y1-xPrxBa2Cu3O7 have been measured over the complete composition range 0